2014
DOI: 10.3727/154427314x14056884441743
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Tourism As a Potential Development Strategy for an Artisanal Fishing Community in the Philippines: The Case of Barangay Victory in Bolinao

Abstract: Development strategies for remote artisanal fishing communities in the less developed world often promote tourism as an alternative livelihood. However, little is known regarding the perspectives of fisherfolk in these communities on tourism as a potential livelihood. Furthermore, there is a paucity of research into fisherfolks' understanding of tourism, how they identify their roles for potential involvement in tourism, and their desire to be "developed." This article reports on a case study of Barangay Victo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 35 publications
(50 reference statements)
0
3
0
2
Order By: Relevance
“…The exploratory two cases described in this study, demonstrate examples of projects that were developed by outsiders without community participation in the planning processes, but with intended social benefits. Previous research has shown that outsiders have the ability to improve business skills and increase knowledge of the tourism sector in developing nations and remote fishing communities (Buckley, 2012;Diedrich, 2007;Porter and Orams, 2014;Towner, 2013). The exploratory case studies also revealed personal private equity investment as an important factor common in both cases.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The exploratory two cases described in this study, demonstrate examples of projects that were developed by outsiders without community participation in the planning processes, but with intended social benefits. Previous research has shown that outsiders have the ability to improve business skills and increase knowledge of the tourism sector in developing nations and remote fishing communities (Buckley, 2012;Diedrich, 2007;Porter and Orams, 2014;Towner, 2013). The exploratory case studies also revealed personal private equity investment as an important factor common in both cases.…”
Section: Discussionmentioning
confidence: 97%
“…There is often a lack of tourism awareness and/or hospitality skills in remote coastal communities (Diedrich, 2007;Porter and Orams, 2014;Saarinen, 2010;Towner, 2013). This lack of awareness of tourism arguably limits the efficacy of community participation in planning process but also a community's ability to fulfil tourist expectations.…”
Section: Discussionmentioning
confidence: 98%
“…Elsewhere in the municipality, large-scale aquaculture of milkfish (Chanos chanos) is widespread, generating pollution impacts throughout the region (San Diego-McGlone et al, 2008;Santanderde Leon et al, 2016). Tourism is also increasingly common in Bolinao, although much less so in Barangay Victory (Porter and Orams, 2014).…”
Section: Study Sitementioning
confidence: 99%
“…Melihat potensi itu, pemerintah, dalam Rancangan Induk Pengembangan Pariwisata nasional (RIPPMAS) 1998, kawasan wisata Mandeh telah ditetapkan sebagai pusat pengembangan wisata bahari untuk wilayah barat Indonesia, bersamaan dengan Biak dan Bunaken pada wilayah Timur ). Perkembangan pariwisata di suatu kawasan dapat meningkatkan kesejahteraan masyarakat lokalnya (Lasso & Dahles, 2020; Porter & Orams, 2014;Then et al, 2021). Untuk itu, diperlukan penggalian seluruh aspek potensi lokal dalam pelestarian wisata bahari sangat dibutuhkan (Alhadi, 2018).…”
Section: Pendahuluanunclassified